Relationship Of FEF25-75, Pefr And SVC With Estrogen And Progesterone Level In Postmenopausal Women - Polly, Zinat Ara; Begum, Shelina; Ferdousi, Sultana; Begum, Noorzahan; Ali, Taskina; Begum, Afroza (Journal of Bangladesh Society of Physiologist, 2012)
Background: Deterioration of lung function is common in women after menopause, which may be related to very low estrogen and progesterone level. Objective: To observe FEF25-75, PEFR and SVC (slow vital capacity) values in apparently healthy postmenopausal women to find out their relationships with serum estrogen and progesterone. Methods: This study was carried out in the Department of Physiology in BSMMU, Dhaka in the year 2007. 30 healthy postmenopausal women aged 45 to 60 years and 30 healthy premenopausal women aged 20 to 30 years during their different phases of menstrual cycle were studied. Postmenopausal women were residents of Dhaka city and premenopausal subjects were medical students. FEF25-75, PEFR and SVC of all subjects were measured by a digital micro spirometer. Their estrogen and progesterone levels were estimated by Micro particle Enzyme Immunoassay (MEIA) method. Data were analyzed by Pearson’s correlation coefficient test, one way ANOVA and unpaired‘t’ test Results: The mean percentage of predicted values of FEF25-75 and PEFR were lower in postmenopausal women compared to those of follicular and luteal phases of premenopausal women but it was not significant. Measured values of SVC was Significantly (p<.001) lower in postmenopausal women compared to those of follicular and luteal phases of premenopausal women. Again Mean serum estrogen and progesterone levels were significantly (p<.001) lower in post menopausal women compared to those of follicular and luteal phases of premenopausal women. In post menopausal women, FEF25-75 was positively, PEFR and SVC were negatively correlated with progesterone level. PEFR and SVC showed positive correlattion and FEF25-75 showed negative correlation with serum estrogen level. All these correlations were statistically non significant. In premenopausal women FEF25-75 and PEFR showed positive correlation and SVC showed negative correlation with serum progesterone level. The relationships were statistically significant in luteal phase but nonsignificant in follicular phase. FEF25-75 ,PEFR and SVC were positively correlated with serum estrogen level in luteal phase but FEF25-75 and PEFR negatively correlated and SVC positively correlated with estrogen level in follicular phase. Conclusion: The outcome of this study shows FEF25-75 , PEFR and SVC may be reduced in postmenopausal women which in turn may be associated with their low progesterone and estrogen levels. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9761 JBSP 2011 6(2): 116-121